Comparison of the combination of dexmedetomidine and ketamine to propofol or propofol/sevoflurane for drug‐induced sleep endoscopy in children. Issue 7 (23rd May 2016) - Kandil, Ali; Subramanyam, Rajeev; Hossain, Mohamed Monir; Ishman, Stacey; Shott, Sally; Tewari, Anurag; Mahmoud, Mohamed
Summary: Aim: Examination of dynamic airway collapse in patients with obstructive sleep apnea (OSA) during drug‐induced sleep endoscopy (DISE) can help identify the anatomic causes of airway obstruction. We hypothesized that a combination of dexmedetomidine and ketamine (Group DK) would result in fewer oxygen desaturations and a higher successful completion rate during DISE in children with OSA when compared to propofol (Group P) or sevoflurane/propofol (Group SP). Methods: In this retrospective study, we reviewed the records of 59 children who presented for DISE between October 2013 and March 2015. Data analyzed included demographics, OSA severity, and hemodynamics (heart rate and blood pressure). The primary outcomes were airway desaturation during DISE to <85% and successful completion of DISE; these were compared between the three groups: DK, P, and SP. Results: Preoperative polysomnography was available for 49 patients. There were significantly more patients with severe OSA in Group P as compared to the other two groups. The mean (±sd ) bolus dose for ketamine, dexmedetomidine, and propofol were 2.0 ± 0.6 mg·kg −1, 1.9 ± 0.9 mcg·kg −1, and 1.8 ± 1.1 mg·kg −1, respectively. The mean (±sd ) infusion rate for dexmedetomidine was 1.6 ± 0.7 mcg·kg −1 ·h −1 and for propofol was 248 ± 68 mcg·kg −1 ·min −1 in Group P and 192 ± 48 mcg·kg −1 ·min −1 in Group SP. Patients in Group DK had significantly fewer desaturations to <85% during DISE compared to Group P. Patients in Group DK had significantly more successful completion of DISE (100% Group DK, 92% Group P, and 79% Group SP) as compared to Group SP. Conclusions: These results suggest that the described dose regimen of propofol used alone or in combination with sevoflurane appears to be associated with more oxygen desaturations and a lower rate of successful completion than a combination of dexmedetomidine and ketamine during DISE in children with OSA. Abstract :